Polyamidoamine Dendrimer-mediated Formulation Development and In Vitro-In Vivo Evaluation of Ketorolac - Prajapati, Ram Narayan (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of study was to explore dendrimer-mediated solubilization of separated ketorolac (KTC) from ketorolac trometamol (KTM) followed by formulation development and in vitro as well as in vivo evaluation. Material and Methods: Amine-terminated polyamidoamine (PAMAM) dendrimers of 3.0G and 4.0G were synthesized and characterized by infrared,1H-NMR spectroscopy. Solubility studies of KTC using G3.0-NH2 and G4.0-NH2 dendrimer were carried out in three different pH values to evaluate the effect of pH on the solubility of KTC. Hemolytic studies and in vitro release rate behavior of optimized formulation DKTC2 were performed. Optimized formulation was further assessed by pharmacodynamic, pharmacokinetics studies along with accelerated stability study. Results and Discussion: The optimized formulation DKTC2 resulted in significant improvements of KTC solubility. The in vitro release rate behavior of KTC from the formulation and stability studies were also favorable. Pharmacodynamic assessment by paw edema model of KTC2 formulation exhibited significant inhibition level (36.82 ± 0.65%) which are higher than those of plain KTC (19.14 ± 0.52 %) after 12 h. Pharmacokinetic study displayed higher AUC0®t; μg/ml/h of 26.514 ± 1.95 with DKTC2, as opposed to 21.945 ± 1.18 with plain KTC. Furthermore, the elimination rate constant of KTC observed with DKTC2 formulation was lower as compared to free KTC, whereas the half-life of KTC experienced with DKTC2 formulation was significantly higher compared to free drug. The designed dendrimer-based system was found to be adequately stable even at elevated temperatures. Conclusion: This study reveals a sustained, high plasma concentration and a slow elimination of the drug that can improve bioavailability, along with helps in the localization of drugs at the inflammatory site and thus provide better therapeutic efficacy at a lower dose.